2019
DOI: 10.1080/02680513.2018.1553707
|View full text |Cite
|
Sign up to set email alerts
|

Sonification of numerical data for education

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Due to the lower spatial density of information that can be reasonably understood tactilely compared to visually [53], and considering the time and effort required to produce tactile graphics [56], educators have increasingly turned toward auditory [74] and multimodal [22,40] ways of teaching data. Interactive audio-tactile systems can improve the educational experience by monitoring student performance [47], offering immediate feedback [47], and fostering engagement through a variety of "fun" interactions [15].…”
Section: Accessible Data Educationmentioning
confidence: 99%
“…Due to the lower spatial density of information that can be reasonably understood tactilely compared to visually [53], and considering the time and effort required to produce tactile graphics [56], educators have increasingly turned toward auditory [74] and multimodal [22,40] ways of teaching data. Interactive audio-tactile systems can improve the educational experience by monitoring student performance [47], offering immediate feedback [47], and fostering engagement through a variety of "fun" interactions [15].…”
Section: Accessible Data Educationmentioning
confidence: 99%
“…Programs are beginning to use artificial intelligence to predict the likelihood of the next spoken word to enable real time translations for widely spoken languages (<www.technologyreview.com/f/612730/googleassistant-now-comes-with-a-real-time-translator-for-27-languages/>). While real-time spoken language translation is currently aspirational for field teaching, it is noteworthy that various forms of translation technologies are already used to increase accessibility for students in STEM, such as speechto-text and text-to-speech (Lee and Templeton 2008), sonograms (visual displays of sound waves, Huffling et al 2018) and sonification (audible versions of data, Vines et al 2019).…”
Section: Real Time Spoken Language Translationmentioning
confidence: 99%
“…The use of sonification techniques and related audio graphs has been shown to aid in conveying information across a wide variety of domain areas. For instance, researchers have found that the presentation of general purpose graphs such as scatterplots [2], line graphs [3], shapes [4], and relational graphs (graphs of relationships modeled with nodes and edges) [5] through sonifications can increase user understanding and retention. Sonification techniques have been used in a broad range of fields; for instance, among many other areas it has been used for exploring and better understanding electroencephalograms (EEGs) [6], neural networks [7], and astronomical images [8].…”
Section: Introductionmentioning
confidence: 99%